Examining Measurement Invariance of a School Climate Survey Across Race and Ethnicity. (December 2021) - Whitehouse, Anna; Zeng, Songtian; Troeger, Rebecca; Cook, Amy; Minami, Takuya
Positive school climate is a key determinant factor of students' psychological well-being, safety, and academic achievement. Although researchers have examined the validity of school climate measures, there is a dearth of research investigating differences in student perceptions of school climate across race and ethnicity. This study evaluated the factor stability of a widely used school climate survey using factor analyses and measurement invariance techniques across racial/ethnic groups. Results of a confirmatory factor analysis indicated a five-factor structure for a school climate survey, and weak measurement invariance was found across Hispanic, Black, and White student groups (ΔCFI = .008). According to paired t tests, significant differences were found among racial/ethnic respondent groups across two factors: teacher and school effectiveness and sense of belonging and care. Validated school climate measures that are culturally and racially responsive to students' experiences allow for accurate interpretations of school climate data. Discussion and implications are provided.